Multimedia technologies as a way to improve the efficiency of the process of teaching foreign languages - Mamurovna, Safarova Nigina (International Journal of Psychosocial Rehabilitation, 2020)
The modern language teachers have new challenges and duties given by the new era. The tradition of English teaching has been drastically changed with the remarkable development of newer technologies such as multimedia technology. Technology provides so many options as it makes teaching interesting and productive because it has capability to attract the language learners. David Graddol states that "technology lies at the heart of the globalization process; a" ecting education work and culture”. thus, technology is one of the most significant drivers of both social and linguistic change.Since there are more and more English learners in Uzbekistan, the language teachers use a variety of teaching methods for effectiveness of their experiment. One method involves the use of technology in English language teaching in order to create English contexts.The rapid development of science and technology such as multimedia technology has offered a better tool to explore the new teaching method. In fact, multimedia technology has played an important role in English language teaching, especially, in the non-native speaking of English situations. Rana argues, "Technology isn't something that students need to be separated from; rather it's something that students need to embrace". Therefore, it helps the students to get involved and learn according to their interests. It has been tested effective and has been widely accepted as a tool for English language teaching around the world. In particular, it has been utilized for the upgrade of modern techniques of language teaching.Nowadays, many academicians and teachers get to know the importance of using different technological devices in both, language teaching and learning processes equally. The new approaches have made language teaching more productive, effective, and interactive. Therefore, the paper aims to analyse the use of technology to foreign language teaching in the non-native speaking countries and to bring out the problems faced by both teachers and learners of English. Further, some exploration of the possibilities to use multimedia technologies for effective teaching of English is to be attempted. Moreover, this study will provide some examples of free language teaching websites